A comparison of physical activity, muscle strength, and sleep between people with type 2 diabetes in Kuwait and the UK: A cross-sectional study - Al Ozairi, Ebaa; Alsaeed, Dalal; Al Roudhan, Dherar; Voase, Nia; Pell, Jill P.; Ho, Frederick K.; Abdulla, Mohammed; Gray, Stuart R. (Frontiers in Endocrinology, 2022)
Background The aim of the current study was to determine the prevalence of low muscle strength and to evaluate physical activity and sleep characteristics in people with type 2 diabetes in Kuwait. Additionally, equivalent data from the UK Biobank cohort were compared. Methods People with type 2 diabetes from the UK Biobank (n = 23,570) and Kuwaiti cohorts (n = 3,135) were included in this cross-sectional study. Self-reported sleep, physical activity, and muscle strength were compared between the cohorts, using linear and logistic regression, with adjustments for age, sex, and duration of diabetes. Results Physical activity levels (−1216 (−1328,1104 Met-min/wee k: standardized B-coefficient −0.52 (−0.57, −0.47) and grip strength (−3.2 (−3.58, −2.82) kg: standardized B-coefficient (−0.29 (−0.32, -0.26) were lower in the Kuwaiti cohort and the odds of having short sleep (OR 1.32 (1.19,1.46), being classed as inactive (OR 8.70 (7.59, 9.98) and having muscle weakness were higher (OR 1.88 (1.69, 2.09). These analyses were adjusted for age, sex, and duration of diabetes. Conclusions This study demonstrates that insufficient sleep, physical inactivity, and muscle weakness are prevalent in people with type 2 diabetes, especially in Kuwait. Importantly, these observations warrant urgent and effective interventions to improve sleep, muscle strength, and physical activity, especially in Kuwait.